Inhibitors of immuno-oncology target HPK1 – a patent review (2016 to 2020). (3rd October 2021) - Linney, Ian D; Kaila, Neelu
ABSTRACT: Introduction : Hematopoietic progenitor kinase (HPK1), a serine/threonine kinase, which is primarily expressed in hematopoietic cells is a negative regulator of T-cell receptor and B cell signaling. Studies using genetic disruption of HPK1 function show enhanced T-cell signaling, cytokine production, and in vivo tumor growth inhibition. This profile of enhanced immune response highlights small molecule inhibition of HPK1 as an attractive approach for the immunotherapy of cancer. Areas covered : This article summarizes the biological rationale for the inhibition of HPK1 as a potential adjunct to the current immuno-oncology (IO) therapies. The article primarily discloses the current state of development of HPK1 inhibitors. Expert Opinion : The rapid increase in the identification of small molecule inhibitors of HPK1 should translate into a fuller understanding of the role of HPK1 inhibition in the IO setting. This understanding will be of huge importance in determining whether HPK1 inhibition alone will be sufficient for tumor growth inhibition or if combination with current IO therapies will be required.